Gilles Deleuze among the New Materialists: Materialist Dialectic versus Neovitalism - Syutkin, Anton (Stasis, 2019)
This article is dedicated to examining the philosophy of Gilles Deleuze in the context of the debates unfolding within contemporary materialism between two currents: materialist dialectic and neovitalism. For the neovitalists (Iain Hamilton Grant and Jane Bennett),Deleuze is a crucial precursor, while for the materialist dialecticians (Alain Badiou, Slavoj Žižek,and others) he is rather an object of critique. This article, however, points to the proximity between Deleuze’s philosophy and none other than materialist dialectic. Paradoxically, this proximity is revealed in Deleuze’s understanding of life, which proposes the division of life into inorganic and organic forms, an affirmative reinterpretation of the death instinct and the necessity of subjective counter-actualization.